Adjuvant effects of curcumin as a photoantimicrobial or irrigant in the non-surgical treatment of periodontitis: Systematic review and meta-analysis - Souza, Eduardo Quintão Manhanini [UNESP]; da Rocha, Tiago Esgalha [UNESP]; Toro, Luan Felipe [UNESP]; Guiati, Isabella Zacarin [UNESP]; Freire, Jéssica de Oliveira Alvarenga [UNESP]; Ervolino, Edilson [UNESP]; Brandini, Daniela Atili [UNESP]; Garcia, Valdir Gouveia; Theodoro, Letícia Helena [UNESP] (Elsevier, 2021)
Aim: Curcumin (CUR) has been used clinically in several studies as a subgingival irrigant or as a photoantimicrobial in combination with a blue light-emitting diode (LED) in antimicrobial photodynamic therapy (aPDT) adjuvant to scaling and root planing (SRP). The aim of this study was to assess the effectiveness of CUR as an irrigant or as a photoantimicrobial in conjunction with the blue LED in aPDT adjuvant to SRP, compared to SRP as conventional mechanical treatment. Materials and methods: Fifteen randomized controlled trials (RCT) were included in a qualitative analysis after researching the databases: PubMed / MEDLINE, SCOPUS, EMBASE, Cochrane Central, Web of Science and Scielo. Manual searches were also performed. Five studies were submitted to quantitative analysis, evaluating periodontal clinical parameters such as probing depth (PD) and clinical attachment level (CAL). Results: The obtained results have shown clinical benefits in PD reduction and CAL gains at 3 months with the use of CUR as adjuvant therapy to SRP, both as an irrigant or photoantimicrobial, in comparison with SRP monotherapy. Conclusion: Currently, there is evidence that treatment with CUR applied as irrigant or in conjunction with the blue LED as aPDT presents superior clinical results in the short term, for clinical periodontics parameters like as PD reduction and CAL gain, when compared to SRP monotherapy in the non-surgical treatment of periodontitis. However, these results cannot be proven in the long term.
Keywords: Antimicrobial photodynamic therapy; Clinical trial; Curcumin; Periodontitis; Systematic review